PROGRAM BIMBINGAN PRIBADI BERDASARKAN PROFIL PRILAKU AGRESIF SISWA SEKOLAH MENENGAH ATAS (STUDI DESKRIPTIP TERHADAP SISWA KELAS XI SMA PGRI 1 BANDUNG TAHUN AJARAN 2011-2012) - Mandar, Hilman Aliy (2012)
The research is motivated phenomenon rampant violence perpetrated students, especially high school students (SMA). Characteristics of aggressive behavior are the focus of this research is aggressive behavior aggressive verbal and non-verbal behavior. The purpose of this study is to obtain a profile of the aggressive behavior of high school students in Class XI PGRI I Bandung and generate personalized mentoring program based on the profile of aggressive behavior in high school feasible PGRI I Bandung for the academic year 2011-2012. The approach used in this study is a quantitative approach is an approach that uses the recording and analysis of research data using statistical calculations. The method used is descriptive method of study that intends to obtain answers about the problems going on with how to process, analyze, interpret and conclude the findings of research. The results of this study show that: 1) the general high school students of class XI PGRI I Bandung School Year 2011-2012 has moderate levels of aggressive behavior and a high percentage of their compliance with 39.3% and 38.6% on indicators of aggressive behavior, 2) high school students of class XI PGRI I Bandung school Year 2011-2012 has a high tendency of aggressive verbal behavior is higher than the non-verbal aggressive behavior, 3) the design of personal guidance program to be implemented at the high school hypothetical PGRI I Bandung. Recommendations given to the research: 1) teacher guidance and counseling in schools is expected to carry out a hypothetical private counseling program which has been designed as a preventive reduksivitas aggressive behavior of students, 2) Department of Educational Psychology and Guidance, expected results of this study can be considered and add insight new in the present study of adolescent behavior in the development of individual subjects, and 3) further research, in order to apply the program which has been designed and can make a personal counseling program more applicable (applicable).